(untitled) (Third Sector Social Economic Review, 2022)
Democracy promotion and democratization has been a crucial issue in the international system especially from the later years of the Cold War. There are multitude of actors promoting democracy based on different theories and focusing on various goals, yet democracy promotion is still evolving both in practice and theory. This study analyzes these changes from historical and political dimensions of democracy promotion. Historically, there are three distinct phases for democracy promotion which have gone through considerable changes due to the goals of the promoters and changes in the international system. Politically, the domestic and international pressures affected the democratization processes and democracy promotion significantly. After evaluating the history and practice of democracy promotion, the recent developments in this area are reviewed. The long and contentious history of democracy promotion could be explained due to the promoters’ ambivalent approaches. It seems that today’s democracy promotion is based on incompatible views and goals. Democracy and democratization are essentially idealist approaches, however contemporary promotion efforts are driven by neorealist views which gives the sceptics of the concept a relatively solid foundation and causes democratization efforts to be less successful.